Locating schemes based on adaptive weighting strategy in heterogeneous wireless networks. (18th November 2013) - Yeh, Sheng–Cheng; Hsu, Wu–Hsiao
Global positioning system (GPS) is the most common technology providing location–based services. When a GPS receiver receives satellite signals, the distance between the satellite and the user is calculated, and then the users current position is located using the triangulation method. However, there is a possibility that landforms, shelters and the number of satellites can have an impact on the satellite signal. This paper combines different heterogeneous wireless networks (i.e., WiFi and ZigBee networks) to improve localisation accuracy, especially when GPS receivers cannot receive a signal. In addition, this paper further demonstrated that combining the WiFi and ZigBee localisation systems achieves almost the same precision as the GPS given without shelter.